A proteção dos direitos das crianças e dos adolescentes nos casos de sequestro internacional : uma análise acerca dos julgamentos proferidos pelo Superior Tribunal de Justiça brasileiro entre os anos de 2007 e 2017 - Holanda, Gabriela Ferreira Pinto de (2018)
The central objective of this study is to analyze if there is an effective protection of children’s and teenager’s rights in cases of international kidnapping. Brazil, one of the signatory countries to the Convention on the Civil Aspects of International Child Abduction, better known as The Hague Convention (1980), since 2000, through Decree no. 3.413 / 2000, uses the Convention as a basis for cases of child abduction or kidnapping, which occurs when the child is taken to another country without the consent of one of the parents, triggering a subsequent custody dispute. The aforementioned international legislation establishes that, when verifying the actual occurrence of abduction or abduction of minors, they must be returned as quickly as possible to the country where they habitually reside, and the superior interest of the children should be prioritized. However, the great question that arises is whether the Brazilian Superior Court of Justice (STJ), when assessing the demands in question, has prioritized the protection of the rights of these vulnerable beings. For the development of the present work, a theoretical research was carried out, which served as a foundation for the construction of the second stage, of an empirical nature, in which a mapping of the decisions rendered by the Brazilian STJ in the last ten years was developed, in the assessment of the claims in which the subtraction or abduction of minors is discussed with the application of the aforementioned convention. With the studies concluded, it is hoped to find the balance point between the application of The Hague Convention and the effective protection of the rights of children and adolescents in the demands arising from illegal subtraction at the international level.